Kedudukan Badan Hukum Rumah Sakit Privat Dihubungkan Dengan Fungsi Sosio Ekonomi - Wahyudi, Wahyudi (Faculty of Sharia, Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia., 2018)
Society as users of health services organized by hospitals are entitled to receive services in plenary by not getting any difference of legal entity of hospital managers. The main goal of health care hospitals include the preventive, curative, rehabilitative and promotive to all levels of society in accordance with the socio-economic function that prioritizes social functioning compared with economic function. The legal entity of hospital management in the form of foundations, associations and limited liability companies. Research in this paper is a normative juridical research, which studied the approach of legislation (the statute approach) means that a problem will be seen from the legal aspect by studying the legislation. And also the method by way of literature study (library research). The research concludes that there are three (3) legal entity that manages private hospitals are more widely used by the public, namely foundations, associations and limited liability companies. Limited liability company that manages the hospital has the main purpose for profit or economic function takes precedence while legal entities of foundations and associations in managing hospitals prioritize socio-economic functions.